THE ENLIGHTENED ABSOLUTISM IN WESTERN EUROPE SOCIETY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Enlightened absolutism represents a state policy which is implemented by the Europeanforces in the duration of the 18th century. The chronological line of the enlightened absolutismcovers the period of almost a half of century, from 1740 until 1789 i.e. to the start of theFrench revolution. The enlightened absolutism is a movement within the absolutism whichfollows after autocracy (fascism) and precedes the despotism. As founder and ideologist of theEnlightened absolutism is considered Thomas Hobbes with his master piece the Leviathan.The Leviathan according to Hobbes is a sovereign state power (the best form for him isabsolute monarchy), which is needed in order to compel people of their obligations. Thephilosophy of this policy amounts to postulate which stipulates that the social reforms arepossible but only through the state and for the state, this phenomena are social expressionof the state interest and the state is the only possible protector of fundamental rights andfreedoms of the man and the citizen is the state. In other words, according to the Enlightenedabsolutists (adherents of the absolute monarchy) ‘welfare in society “is possible only andonly through the state and the regime that was established by the same. Because of all abovemention, our interest in this paper is to explain the basic goal of the ideas of the enlightenedabsolutism.